Construction of interactive health education model for adolescents based on affective computing - Chen, Xieping; Zhang, Yu; Xie, Qian (Frontiers in Psychology, 2022)
At present, people mainly focus on health education of adolescents. The health education of adolescents is related to the future of adolescents. In youth, their emotions are easily influenced. Therefore, this paper constructs an interactive health education model for adolescents through affective computing. Researchers in various countries have done a lot of research on human-computer interaction, and affective computing is one of the research hotspots. This paper aims to study the use of affective computing to construct an interactive health education model for adolescents. It proposed an interactive emotional algorithm based on emotional computing, and focuses on the ICABoost algorithm. The experimental results of this paper show that the surveyed junior high school students are divided into three grades: the first, second and third grades. Among them, 11, 11, and 13 were mentally healthy, with a total percentage of only 18.5%. 16, 14 and 16 were moderately severe in health education, accounting for 24.3%. The percentage of severe severe cases was 29.6%. It can be seen that, through the investigation of this paper, it can be seen that today's youth health education should be paid attention to. Only by constructing a corresponding interactive health education model for adolescents can adolescents develop in an all-round way.